Vignette Research Research Methods - Agostini, Evi (Bloomsbury Research Methods, 2024)
This open access book introduces vignette research to new and experienced researchers by guiding them through its history, theory and underlying principles before delving into step-by-step practical guidance on how to do vignette research. Vignette research is an innovative qualitative, narrative and phenomenological research methodology that has gained international recognition, sparking interest from a wide range of individuals and institutions in global contexts. Vignettes are concise narratives, which capture human experiences in real life settings. They reveal surprising or intriguing facets and intangible moments. The experiential narratives resonate with readers and reduce the distance between the researcher and the researched. The ebook editions of this book are available open access under a CC-BY 4.0 licence on bloomsburycollections.com. Open access was funded by the Austrian Science Fund (FWF).